2016
DOI: 10.1007/s00330-016-4218-5
|View full text |Cite
|
Sign up to set email alerts
|

Lung morphology assessment of cystic fibrosis using MRI with ultra-short echo time at submillimeter spatial resolution

Abstract: • Spatial resolution of lung MRI is limited using non-ultra-short TE MRI technique • Ultra-short echo time (UTE) technique enables submillimeter 3D-MRI of airways • 3D-UTE MRI shows very good concordance with CT in assessing cystic fibrosis • Radiation-free 3D-UTE MRI enables the Helbich-Bhalla scoring without a need for contrast injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
88
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 44 publications
1
88
0
2
Order By: Relevance
“…3D radial UTE proton MRI can depict the pulmonary parenchymal structural changes of CF in a similar way to CT . A recent study demonstrates that the UTE signal intensity of the lungs is reproducible and significantly correlated with CT measures of emphysema and PFTs in chronic obstructive pulmonary disease .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…3D radial UTE proton MRI can depict the pulmonary parenchymal structural changes of CF in a similar way to CT . A recent study demonstrates that the UTE signal intensity of the lungs is reproducible and significantly correlated with CT measures of emphysema and PFTs in chronic obstructive pulmonary disease .…”
Section: Discussionmentioning
confidence: 98%
“…A recent study demonstrated that the UTE signal–intensity measurements of the lung are reproducible and significantly correlated with computed tomography (CT) measures of emphysema and pulmonary function testing in human subjects with chronic obstructive pulmonary disease . Moreover, UTE proton MRI has been recently shown to have favorable comparison to CT findings of lung structural changes in subjects with evidence of cystic fibrosis (CF) …”
mentioning
confidence: 99%
“…Recently, ultrashort echo time (UTE) MRI with 3D radial k ‐space trajectories has shown promise in overcoming these obstacles. However, experience with 3D radial UTE chest MR is limited to animal models and small human studies, mostly in adults . Moreover, 3D radial acquisitions suffer from inherent inefficiencies in fully populating k ‐space, leading to trade‐offs between longer scan times and data undersampling with lesser resolution …”
mentioning
confidence: 99%
“…The development of ultrashort echo time (UTE) acquisition has enabled obtaining sufficient signal in the parenchyma despite the short T 2 *, while recent technical developments have allowed 3D acquisitions with high spatial resolution . Multiple studies have demonstrated nowadays an interest in noncontrast‐enhanced UTE for the evaluation of various pulmonary and airway disorders, including nodules or masses, ground glass opacity, micronodules, nodules, patchy shadow or consolidation, emphysema or bullae, bronchiectasis, reticular opacity, honeycomb, and traction bronchiectasis . Besides pulmonary disease, UTE imaging has also been evaluated in other regions of the body, with a potential in qualitative and quantitative assessment in the musculoskeletal system, but without current use in routine practice.…”
mentioning
confidence: 99%